Preparation method of calcium carbonate carbon dot fluorescent powder and ultraviolet aging resistant fluorescent sealant
By adding specially prepared calcium carbonate fluorescent carbon spots to seal glue, prepare calcium carbonate carbon dot fluorescent powder, solve the problem of sealing glue in long -term exposure to the aging of sunlight, and realize the ultraviolet aging and fluorescent performance of sealing glue Improvement.
Patent Information
- Application Number
- CN202411494260.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-28
AI Technical Summary
The existing sealant is prone to aging under long-term exposure to sunlight. The ultraviolet absorbers added to the prior art are toxic, complex in production, high purity requirements, and difficult to achieve the purpose of resistance to ultraviolet aging.
By adding specially prepared calcium carbonate fluorescent carbon points, prepare a kind of calcium carbonate carbon dot fluorescent powder, and apply it to the sealing glue. The fluorescent powder is prepared by the drip reaction method of water heat reaction and carbonate solution. Essence
It significantly improves the ultraviolet aging performance of sealing gels and has good fluorescent performance, so that sealing has maintained more than 90%before aging.
Smart Images

Figure CN119371963A_ABST
Abstract
Description
Technical Field
[0001] The invention mainly relates to the field of sealants, and in particular to a preparation method of calcium carbonate carbon dot fluorescent powder and ultraviolet aging-resistant fluorescent sealant. Background Art
[0002] Silane-modified polyether sealants have been applied in many fields due to their good adhesion, environmental protection, excellent weather resistance and paintability, and have become the fastest-growing sealant product at home and abroad in recent years. However, when they are used in places exposed to sunlight for a long time, they are prone to aging and thus damage the material. In the prior art, ultraviolet absorbers are usually added to improve their resistance to ultraviolet radiation. Common organic small molecule ultraviolet absorbers on the market, such as 2-hydroxy-4-n-octyloxybenzophenone, 2-(2'-alkyl-3',5'-di-tert-phenyl)-5-chlorobenzotriazole, 2,4-dihydroxybenzophenone, etc., are toxic in themselves, have complex production processes, high purity requirements, and very narrow ultraviolet absorption ranges. They are easily photodegraded or decomposed under long-term ultraviolet radiation; and existing inorganic ultraviolet absorbers such as titanium dioxide, zinc oxide, etc., although they have a wide absorption range, will accelerate the aging process of the material and reduce the mechanical properties of the sealant. Therefore, it is difficult for the sealants in the prior art to achieve the purpose of ultraviolet aging resistance. Summary of the invention
[0003] The main purpose of the present invention is to provide a UV-resistant sealant and a preparation method. By adding specially prepared calcium carbonate fluorescent carbon dots, the sealant can significantly improve the UV-resistant performance and have good fluorescence performance, thereby overcoming the technical defect that the prior art sealant in the background technology is difficult to resist UV-resistant. The secondary purpose of the present invention is to provide a preparation method of calcium carbonate fluorescent carbon dots, which is used to provide the calcium carbonate fluorescent carbon dots in the aforementioned sealant preparation method. The present invention also provides the application of calcium carbonate fluorescent carbon dots, which are prepared by the aforementioned preparation method of calcium carbonate fluorescent carbon dots.
[0004] To achieve the above object, the present invention provides a method for preparing calcium carbonate carbon dot phosphor, comprising the following steps:
[0005] S1, adding anhydrous citric acid and cysteine hydrochloride in a weight ratio of 10:1-4 into water to dissolve, and then transferring to a reactor for hydrothermal reaction. After the reaction is completed, cooling to room temperature, centrifuging, filtering and freeze-drying the product to obtain carbon dot powder;
[0006] S2, dissolving the carbon dot powder in the calcium salt solution and stirring evenly to obtain a mixed solution;
[0007] S3, adding the mixed solution obtained in S2 dropwise into the carbonate solution, stirring the reaction to obtain a solid precipitate, and washing and drying the solid precipitate to obtain a calcium carbonate carbon dot phosphor.
[0008] Centrifugation and membrane separation are common separation technologies. Centrifugation refers to placing the mixture in a centrifuge and using the centrifugal force to separate the different components in the mixture into layers; membrane separation refers to placing the mixture on a semipermeable membrane and using the pores of the membrane and the molecular weight, charge, solubility and other properties of the substance to separate the different substances through the membrane.
[0009] The present application obtains carbon dot powder by controlling the weight ratio of anhydrous citric acid: cysteine hydrochloride, which can effectively regulate the ratio of amino and carboxyl groups on the surface of carbon dots, and then regulate its ultraviolet absorption performance. The carbon dot powder is dissolved in a calcium salt solution again, and a mixed solution is added dropwise to a carbonate solution for reaction. A calcium carbonate carbon dot phosphor with good fluorescence performance and beneficial to improving the ultraviolet aging resistance of the sealant is prepared by a simple and fast preparation method. The fluorescence quantum yield of the calcium carbonate carbon dot phosphor prepared in the present invention is in the range of 50-85%, and the ultraviolet absorption range is 300-390nm.
[0010] Preferably, the water in step S1 is distilled water or deionized water.
[0011] Preferably, in step S1, the dissolution is performed by ultrasonic dissolution, the hydrothermal reaction is performed by heating at 170 to 200°C for 7 to 9 hours, and the inner liner coating of the reactor is polytetrafluoroethylene. Ultrasound can effectively dissolve anhydrous citric acid and cysteamine hydrochloride in water, which is beneficial to the subsequent hydrothermal reaction. The preferred reaction temperature and duration are conducive to the complete hydrothermal reaction. Polytetrafluoroethylene has good acid and alkali corrosion resistance and high chemical stability, and is suitable as the inner liner coating of the reactor in this solution.
[0012] Preferably, in step S2, the carbon dot mass concentration of the mixed solution is 0.002-20 mg / ml. Preferably, this carbon dot mass concentration is beneficial to calcium carbonate encapsulating the carbon dots. When the carbon dot mass concentration is too high, the excess carbon dots cannot be encapsulated by calcium carbonate, resulting in waste.
[0013] Preferably, in step S2, the calcium salt solution is an aqueous solution containing at least one of calcium nitrate, calcium nitrite and calcium chloride as a solute. The aqueous solution of the above preferred solute is used as the calcium salt solution, which is conducive to the combination of carbon dots and calcium ions through electrostatic interaction, so that it is easier to be loaded when preparing the phosphor.
[0014] Preferably, in step S3, the carbonate is an aqueous solution containing at least one of sodium carbonate, potassium carbonate, sodium bicarbonate and potassium bicarbonate as a solute.
[0015] The present invention proposes an application of calcium carbonate carbon dot phosphor, which is prepared by the preparation method of calcium carbonate carbon dot phosphor in the above scheme and is used as a raw material component in the preparation of sealant to improve the ultraviolet aging performance of the sealant and significantly reduce the ultraviolet aging attenuation degree of the mechanical properties of the sealant.
[0016] The present invention provides a UV-resistant fluorescent sealant, wherein the sealant raw materials include the following components in parts by mass:
[0017] The calcium carbonate carbon dot phosphor in the above scheme comprises 20 to 120 parts, 50 to 110 parts of silane-modified polyether prepolymer, 30 to 50 parts of polypropylene glycol, 0.5 to 1.5 parts of organic tin catalyst and 1 to 2 parts of 3-(aminopropyl)trimethoxysilane. The calcium carbonate carbon dot phosphor is used in sealants, and has excellent fluorescence performance and UV aging resistance, and can maintain more than 90% of the tensile strength and elongation at break performance before aging after aging.
[0018] Preferably, the organotin catalyst is at least one of dibutyltin dilaurate, dioctyltin diacetate and stannous octoate.
[0019] The invention provides a method for preparing a fluorescent sealant resistant to ultraviolet aging. The sealant raw materials are mixed and reacted under vacuum conditions to obtain the fluorescent sealant resistant to ultraviolet aging.
[0020] Preferably, the reaction temperature of the sealant raw material is 50 to 100° C. and the reaction pressure is -0.01 to -0.1 MPa. The above preferred reaction temperature and negative pressure conditions are conducive to the normal preparation of the sealant and the removal of water to avoid cross-linking and curing.
[0021] The present application obtains carbon dot powder by controlling the weight ratio of anhydrous citric acid: cysteine hydrochloride, which can effectively regulate the ratio of amino and carboxyl groups on the surface of carbon dots, and then regulate its ultraviolet absorption performance. Then the carbon dot powder is dissolved in a calcium salt solution, and the mixed solution is added dropwise to a carbonate solution for sufficient reaction. A calcium carbonate carbon dot phosphor is prepared by a simple and fast preparation method, which is used as a sealant raw material, and a silane-modified polyether prepolymer is selected as a base material, and polypropylene glycol, an organic tin catalyst and 3-(aminopropyl) trimethoxysilane are compounded. The sealant obtained has excellent fluorescence performance and can significantly improve the ultraviolet aging resistance of the sealant, so that the degree of mechanical property attenuation of the sealant before and after aging is significantly reduced, and the mechanical properties after aging remain above 90% of those before aging. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying any creative work.
[0023] Figure 1 The graphs of calcium carbonate carbon dot phosphor under daily light (a) and ultraviolet light (b);
[0024] Figure 2 Figure 2 shows the UV-resistant sealant under daily light (a) and UV light (b).
[0025] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in this field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0027] In the following examples and comparative examples, raw materials, reagents, etc., unless otherwise specified, were obtained from commercial sources, and the same batch of raw materials or reagents were used in the examples and comparative examples.
[0028] In the specific implementation of the present invention, the various performance indicators of the calcium carbonate carbon dot phosphor and the sealant are measured by the following methods or standards:
[0029] 1. UV aging resistance
[0030] UV aging conditions: in accordance with GB / T 16422-2022 "Plastics Laboratory Light Source Exposure Test Method" standard.
[0031] The UV aging resistance is determined by testing the changes in the tensile strength and elongation at break of the material before and after UV aging.
[0032] (1) Tensile strength, test method: refer to GB / T528-2009 "Vulcanized rubber or thermoplastic rubber-Determination of tensile stress-strain properties".
[0033] (2) Elongation at break, test method: refer to GB / T528-2009 "Vulcanized rubber or thermoplastic rubber - Determination of tensile stress-strain properties".
[0034] 2. Ultraviolet absorption range
[0035] Determination method: The absorption spectrum of carbon dots was measured by UV-1900 ultraviolet-visible spectrometer.
[0036] 3. Fluorescence quantum yield
[0037] Determination method: Calculation of fluorescence quantum yield (QY) The calculation formula of QY is as follows:
[0038]
[0039] Wherein the subscripts ST and X represent the standard quinine sulfate and the test sample, respectively, φ represents the fluorescence quantum yield, Grad represents the ratio of the integral area of the fluorescence emission spectrum to the absorbance, and η represents the refractive index of the solvent. In order to reduce the influence of reabsorption, the absorbance of the 10 mm fluorescence cuvette at the excitation wavelength of the sample shall not exceed 0.1.
[0040] Example 1
[0041] (1) Preparation of carbon dots:
[0042] Weigh 10.0 g of anhydrous citric acid and 2.0 g of cysteamine hydrochloride, dissolve in 50.0 mL of deionized water, add to a 100 mL hydrothermal reactor after ultrasonic dissolution, and heat at 180°C for 8 h. After the reaction is completed, cool to room temperature, centrifuge, filter, and freeze-dry the product to obtain carbon dots for use.
[0043] Prepare 500 mL of 1.0 mol / L CaCl2 solution, add 5.0 g of carbon dots, dissolve by ultrasonication, and after the reaction is completed, add the mixed solution dropwise into Na2CO3 (1 mol / L, 500 mL) solution. After the addition is completed, continue stirring for 1 hour. After the reaction is completed, wash and dry the solid precipitate to obtain calcium carbonate carbon dot phosphor.
[0044] (2) Sealant preparation:
[0045] According to the ratio in the table below, the mixture was fully mixed and reacted for 1 hour under vacuum conditions at a temperature of 40°C and a pressure of -0.09 MPa to obtain a sealant.
[0046]
[0047] Comparative Example 1
[0048] The preparation method of the sealant and carbon dots in this comparative example refers to Examples 1-4, except that: in step S2, the mass of anhydrous citric acid is 10 g, the mass of cysteine hydrochloride is 0.5 g, and the weight ratio of anhydrous citric acid:cysteine hydrochloride is 10:0.5.
[0049] Example 2
[0050] The preparation method of the sealant and carbon dots of this embodiment refers to that of Embodiments 1-4, except that in step S2, the mass of anhydrous citric acid is 10 g, the mass of cysteine hydrochloride is 1 g, and the weight ratio of anhydrous citric acid:cysteine hydrochloride is 10:1.
[0051] Example 3
[0052] The preparation method of the sealant and carbon dots of this embodiment refers to that of Embodiments 1-4, except that in step S2, the mass of anhydrous citric acid is 10 g, the mass of cysteine hydrochloride is 4 g, and the weight ratio of anhydrous citric acid:cysteine hydrochloride is 10:4.
[0053] Comparative Example 2
[0054] The preparation method of the sealant and carbon dots in this comparative example refers to Examples 1-4, except that: in step S2, the mass of anhydrous citric acid is 10 g, the mass of cysteine hydrochloride is 8 g, and the weight ratio of anhydrous citric acid:cysteine hydrochloride is 10:8.
[0055] Example 4
[0056] (1) Preparation of carbon dots:
[0057] Weigh 10g of anhydrous citric acid and 3g of cysteamine hydrochloride, dissolve in 50.0mL of deionized water, add to a 100mL hydrothermal reactor after ultrasonic dissolution, and heat at 180°C for 8h. After the reaction is completed, cool to room temperature, centrifuge, filter, and freeze-dry the product to obtain carbon dots for use.
[0058] Prepare 500 mL of 1.0 mol / L CaCl2 solution, add 5.0 g of carbon dots, dissolve by ultrasonication, and after the reaction is completed, add the mixed solution dropwise into Na2CO3 (1 mol / L, 500 mL) solution. After the addition is completed, continue stirring for 1 hour. After the reaction is completed, wash and dry the solid precipitate to obtain calcium carbonate carbon dot phosphor.
[0059] (2) Sealant preparation:
[0060] According to the ratio in the table below, the mixture was fully mixed and reacted for 1 hour under vacuum conditions at a temperature of 40°C and a pressure of -0.09 MPa to obtain a sealant.
[0061]
[0062]
[0063] Comparative Example 3
[0064] The preparation method of the sealant and carbon dots in this comparative example refers to that of Examples 1-4, except that no calcium carbonate carbon dot phosphor is added to the sealant composition.
[0065] Comparative Example 4
[0066] The preparation method of the sealant and carbon dots in this comparative example refers to that of Examples 1-4, except that calcium carbonate is used in place of calcium carbonate carbon dot phosphor in the sealant component.
[0067] Comparative Example 5
[0068] The preparation method of the sealant and carbon dots in this comparative example refers to that of Examples 1-4, except that: the calcium carbonate carbon dot phosphor is replaced by ordinary carbon dot phosphor in the sealant component; the ordinary carbon dot phosphor is prepared by adding citric acid and glycine in a weight ratio of 10:3 into deionized water for ultrasonic dissolution, and then transferring to a reactor for hydrothermal reaction; after the reaction is completed, cooling to room temperature; the product is centrifuged, filtered through a membrane, and then freeze-dried to obtain carbon dot powder.
[0069] Comparative Example 6-1
[0070] The preparation method of the sealant and carbon dots in this comparative example refers to Example A, except that the calcium carbonate carbon dot phosphor is replaced by an organic ultraviolet absorber in the sealant component, and the organic ultraviolet absorber is selected from 2-(5-chloro-2-benzotriazolyl)-6-tert-butyl-p-cresol.
[0071] Comparative Example 6-2
[0072] The preparation method of the sealant and carbon dots in this comparative example refers to that in Example A, the difference is that the calcium carbonate carbon dot phosphor is replaced by an inorganic ultraviolet absorber in the sealant component, and the inorganic ultraviolet absorber is selected from titanium dioxide.
[0073] After testing, the products obtained in the above specific embodiments and comparative examples have various performance data as shown in the following table:
[0074]
[0075]
[0076] From the data in the above table, we can conclude that:
[0077] It can be seen from Examples 1-1 to 1-5 that when the raw materials of the sealant of the present application include, by weight, 20 to 120 parts of calcium carbonate carbon dot phosphor, 50 to 110 parts of silane-modified polyether prepolymer, 30 to 50 parts of polypropylene glycol, 0.5 to 1.5 parts of organic tin catalyst and 1 to 2 parts of 3-(aminopropyl)trimethoxysilane, and the weight ratio of anhydrous citric acid to cysteine hydrochloride is in the range of 10:1 to 4, the fluorescence performance and ultraviolet aging performance of the prepared sealant are both good. In terms of fluorescence performance, its ultraviolet absorption range is 300 to 390 nm, and the ultraviolet aging attenuation of mechanical properties is significantly reduced, reaching more than 90% of the mechanical properties before aging, and the tensile strength before aging reaches 0.3 to 1.2 MPa, and the elongation at break reaches 270 to 890%.
[0078] Comparing Examples 1-4, Examples 2-3 and Comparative Examples 1-2, it can be seen that as the weight ratio of anhydrous citric acid: cysteine hydrochloride changes in the range of 10:0.5-10:8, the tensile strength of the sealant before aging, the elongation at break before aging, the change in tensile strength, the change in elongation at break, and the fluorescence quantum yield of the calcium carbonate phosphor all show a trend of first increasing and then decreasing. When the weight ratio of anhydrous citric acid: cysteine hydrochloride is lower than 10:1, such as in Comparative Example 1, it can be seen that the fluorescence quantum yield of the calcium carbonate phosphor drops to 20%, and the tensile strength change of the sealant after UV aging is It drops to 75.36% before aging, and the elongation at break drops to 80.68% before aging. When the weight ratio of anhydrous citric acid: cysteine hydrochloride is higher than 10:4, as in Comparative Example 2, it can be seen that the ultraviolet absorption range of the calcium carbonate phosphor shifts to the right, and the fluorescence yield drops to 24%. The tensile strength of the sealant after ultraviolet aging drops to 89.23% before aging, and the elongation at break drops to 75.50% before aging. It can be seen that the weight ratio of anhydrous citric acid and cysteine hydrochloride in the calcium carbonate phosphor in this application significantly affects the fluorescence quantum yield and the degree of ultraviolet aging attenuation resistance of the sealant.
[0079] The sealant of Example 4 has the best mechanical properties before aging, the lowest degree of mechanical property attenuation after ultraviolet aging, the best ultraviolet absorption range and fluorescence quantum yield of calcium carbonate phosphor, and the best comprehensive performance.
[0080] By comparing Examples 1-4 with Comparative Examples 4 and 5, it can be seen that the addition of calcium carbonate to the sealant can only serve as a filler and cannot make the sealant produce fluorescent properties. Compared with the sealant added with calcium carbonate fluorescent carbon dot powder, the ultraviolet aging resistance of the sealant added with calcium carbonate is significantly reduced; although the conventionally prepared carbon dot fluorescent powder is added to the sealant component to make the sealant produce fluorescent properties, the ultraviolet absorption range of its fluorescent carbon dot powder is relatively narrow, and the fluorescence quantum yield is significantly lower than that of Examples 1-4 with the addition of calcium carbonate fluorescent carbon dot powder, and the ultraviolet aging resistance is significantly reduced compared with Examples 1-4 with the addition of calcium carbonate fluorescent carbon dot powder.
[0081] By comparing Examples 1-4 with Comparative Examples 3 and Comparative Examples 6-1 to 6-2, it can be seen that when no ultraviolet absorber is added to the sealant composition, such as Comparative Example 3, the mechanical properties of the sealant are significantly attenuated by ultraviolet aging, the tensile strength before aging is 0.24 MPa, and the elongation at break before aging is 245%, which are significantly lower than those of Examples 1-4; when conventional organic ultraviolet absorbers are added, such as Comparative Example 6-1, the ultraviolet absorption range is shifted to the left relative to Example 1-4, and the ultraviolet absorption range is narrowed, and the degree of ultraviolet aging attenuation of the mechanical properties of the sealant is significantly higher than that of Example 1-4; when conventional inorganic ultraviolet absorbers are added, such as Comparative Example 6-2, the ultraviolet absorption range is shifted to the left relative to Example 1-4, and the ultraviolet absorption range is wider, but it is not resistant to ultraviolet aging. After ultraviolet aging, the sealant undergoes cross-linking and hardening, so the tensile strength is significantly improved, but the elongation at break is reduced to 44.75% before aging, and Examples 1-4 in which calcium carbonate fluorescent carbon dot powder is added have excellent performance in both the ultraviolet absorption range and the mechanical properties of the sealant and the ultraviolet aging resistance.
[0082] To sum up, compared with existing conventional organic UV absorbers and conventional inorganic UV absorbers, calcium carbonate fluorescent carbon dot powder can have a comparable or even wider UV absorption range. At the same time, the UV aging attenuation of mechanical properties is significantly reduced, that is, the UV aging resistance of the sealant is significantly improved, and the service life of the sealant under UV conditions is increased. On the other hand, the calcium carbonate fluorescent carbon dot powder in this application is not a simple substitute for calcium carbonate or conventional fluorescent carbon dot powder. Adding calcium carbonate or conventional fluorescent carbon dot powder to the raw material composition of the sealant cannot significantly improve the UV aging resistance of the sealant.
[0083] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for preparing calcium carbonate carbon dot phosphor, characterized in that: The following steps are involved: S1, adding anhydrous citric acid and cysteine hydrochloride in a weight ratio of 10:1-4 into water to dissolve, and then transferring to a reactor for hydrothermal reaction. After the reaction is completed, cooling to room temperature, centrifuging the product, passing through a membrane, and freeze-drying to obtain carbon dot powder; S2, dissolving the carbon dot powder in the calcium salt solution and stirring evenly to obtain a mixed solution; S3, adding the mixed solution obtained in S2 dropwise into the carbonate solution, stirring the mixture to react completely to obtain a solid precipitate, and washing and drying the solid precipitate to obtain a calcium carbonate carbon dot phosphor.
2. The method for preparing the calcium carbonate carbon dot phosphor according to claim 1, characterized in that: In step S2, the mass concentration of carbon dots in the mixed solution is 0.002-20 mg / ml.
3. The method for preparing the calcium carbonate carbon dot phosphor according to claim 1, characterized in that: In step S1, anhydrous citric acid and cysteine hydrochloride are in a weight ratio of 10:
3.
4. The method for preparing the calcium carbonate carbon dot phosphor according to claim 1, characterized in that: In step S1, the dissolution is performed by ultrasonic dissolution, the hydrothermal reaction is performed at a temperature of 170 to 200° C. for 7 to 9 hours, and the inner liner coating of the reactor is polytetrafluoroethylene; in step S2, the calcium salt solution is an aqueous solution containing at least one of calcium nitrate, calcium nitrite and calcium chloride as a solute; in step S3, the carbonate solution is an aqueous solution containing at least one of sodium carbonate, potassium carbonate, sodium bicarbonate and potassium bicarbonate as a solute.
5. Application of calcium carbonate carbon dot phosphor, characterized in that: The calcium carbonate carbon dot phosphor prepared by the preparation method according to any one of claims 1 to 4 is used as a raw material component in the preparation of sealant.
6. UV-resistant fluorescent sealant, characterized in that: The sealant raw materials are calculated by weight. Includes the following components: 20 to 120 parts of calcium carbonate carbon dot phosphor prepared by the preparation method according to any one of claims 1 to 4, 50 to 110 parts of silane-modified polyether prepolymer, 30 to 50 parts of polypropylene glycol, 0.5 to 1.5 parts of organic tin catalyst and 1 to 2 parts of 3-(aminopropyl)trimethoxysilane.
7. The UV-resistant fluorescent sealant according to claim 6, characterized in that: The sealant raw material comprises the following components in parts by mass: 100 parts of calcium carbonate carbon dot phosphor, 100 parts of silane-modified polyether prepolymer, 50 parts of polypropylene glycol, 1 part of dibutyltin dilaurate and 1 part of 3-(aminopropyl)trimethoxysilane.
8. The method for preparing the UV-resistant fluorescent sealant according to claim 6, characterized in that: The organotin catalyst is at least one of dibutyltin dilaurate, dioctyltin diacetate and stannous octoate.
9. The method for preparing the UV-resistant fluorescent sealant according to any one of claims 6 to 8, characterized in that: The sealant raw materials are mixed and reacted under a vacuum state to obtain the ultraviolet aging-resistant fluorescent sealant.
10. The method for preparing the UV-resistant fluorescent sealant according to claim 9, characterized in that: The reaction temperature of the sealant raw material is 50-100° C., and the reaction pressure is -0.01-0.1 MPa.
Citation Information
Cited By
Ultra-dull polyester fiber and preparation method thereof
CN120250184A